Productivity and Feasibility of Lift-net Fishery in Kwandang - Frengky Armain; Abd Hafidz Olii; Alfi Sahri Baruadi (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
The purpose of this study is to determine productivity and business feasibility of lift-net boat. The method used is a survey method with productivity and business feasibility analysis. The results showed that the lift-net boat productivity was 143.19 kg / GT. The feasibility of lift-net boats that lands their catch in the Kwandang Nusantara Fisheries Port (PPN) based on the Revenue Cost Ratio (R / C) value of 1.39; Payback Period (PP) 1.06 years or 1 year 22 days, and NVP + Rp. 301,768,360. This shows that lift-net boat fishery is feasible. Keywords: productivity; feasibility; lift-net; fishery.